Antifouling and antibacterial ceramic-like coating and preparation method thereof
By introducing specific ingredients into UV-cured imitation ceramic coatings, the antifouling and antibacterial properties of the coating are improved, solving the problems of easy staining and insufficient antibacterial performance of existing coatings, and achieving an efficient antifouling, antibacterial and wear-resistant coating. layer effect.
Patent Information
- Application Number
- CN202411602323.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Existing UV cured imitation ceramic coatings are prone to stains, are difficult to clean, and have insufficient antibacterial performance, making it difficult to meet the high standards of health and safety of modern consumers.
By introducing ingredients such as UV-curable fingerprint easy-to-clean fluorine-containing resin, hybrid silicone-fluorine polyurethane acrylic, nano-zinc oxide, eugenol, terpineol and cyclohexanone, the antifouling performance, antibacterial performance and wear resistance of the coating are improved.
The coating achieves antifouling and antibacterial capabilities and a high-hardness ceramic texture. It has a self-cleaning effect and maintains surface hygiene for a long time. It is suitable for promotion and application in high-end markets such as automotive interiors and home appliance casings.
Smart Images

Figure BDA0005128627310000061 
Figure BDA0005128627310000071 
Figure BDA0005128627310000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an antifouling and antibacterial imitation ceramic coating and a preparation method thereof. Background Art
[0002] Imitation ceramic coating, as an innovative material that combines aesthetics and practicality, has attracted much attention for its high gloss and high hardness characteristics, as well as its ability to give the surface of objects a delicate texture similar to ceramic. In the field of automotive interiors, imitation ceramic coatings can not only significantly enhance the luxury and overall aesthetics of the interior, but its excellent wear resistance and scratch resistance can also effectively resist wear and tear in daily use and extend the service life of interior parts. Similarly, its application on the outer shell of home appliances not only makes the product appearance more beautiful and fashionable, but also enhances the hardness of the surface, reduces scratches caused by daily cleaning or minor collisions, and keeps home appliances as new for a long time. Existing anti-ceramic coatings generally use high-temperature curing or UV curing to achieve curing. High-temperature curing is often limited to the application scenario, while UV curing has become the preferred choice in many fields due to its high efficiency and environmental protection, especially in today's pursuit of rapid production and energy conservation and emission reduction.
[0003] However, the UV-curable ceramic-like coatings widely used in the current market have a problem that cannot be ignored: they are often easily stained and difficult to clean. Once the surface is scratched, the aesthetics will be greatly reduced. These problems not only affect the user experience, but also limit the further expansion of ceramic-like coatings in the high-end market. More importantly, with the continuous improvement of the quality of life in modern society, consumers' pursuit of healthy life is increasing. For items that are frequently touched in daily life, such as car interiors and home appliance housings, their antibacterial properties have become a new focus. Traditional ceramic-like coatings have mediocre antibacterial performance and are difficult to meet the market's high standards for health and safety.
[0004] Therefore, the development of a new type of ceramic-like coating with excellent anti-fouling and antibacterial capabilities has become an urgent need in the industry. Summary of the invention
[0005] In order to develop a new type of imitation ceramic coating with excellent antifouling and antibacterial capabilities, the present application provides an antifouling and antibacterial imitation ceramic coating and a preparation method thereof. The present application found in the research that by introducing specific fluorine-containing resins and hybrid silicone-fluorine polyurethane acrylics, the antifouling performance and wear resistance of the coating can be significantly improved. By adding nano zinc oxide, cyclohexanone, eugenol, and pinene alcohol, the coating can be given a good antibacterial effect and further improve the wear resistance of the coating, so that the coating can have both antifouling and antibacterial capabilities and a high-hardness ceramic texture.
[0006] In the first aspect, the present application provides an antifouling and antibacterial imitation ceramic coating using the following technical solutions: An antifouling and antibacterial imitation ceramic coating comprises the following components in percentage by mass: 30%-40% of UV-curable fingerprint easy-to-clean fluorine-containing resin, 25%-30% of UV-curable hybrid silicon-fluorine polyurethane acrylic, 8%-12% of tripropylene glycol diacrylate, 2%-4% of neopentyl glycol diacrylate, 3%-6% of photoinitiator, 3%-5% of dispersant, 3%-5% of nano silicon carbide, 1%-2% of nano zinc oxide, 1%-2% of eugenol, 1%-2% of pine alcohol, 2%-3% of cyclohexanone and 10%-20% of organic solvent.
[0007] In the above technical scheme, the present application can effectively improve the antifouling performance of the coating by selecting UV-curable fingerprint easy-to-clean fluorine-containing resin as the main material of the antifouling and antibacterial imitation ceramic coating. The introduction of UV-curable hybrid silicon-fluorine polyurethane acrylic gives the coating good wear resistance, weather resistance and chemical resistance. The introduction of tripropylene glycol diacrylate and neopentyl glycol diacrylate further enhances the hydrophobicity, adhesion and wear resistance of the coating. The introduction of nano-silicon carbide gives the coating a simulated ceramic texture. The addition of nano-zinc oxide, eugenol and pineneol gives the coating a wide range of The antibacterial properties of the coating spectrum can effectively inhibit the growth and reproduction of bacteria and improve the antibacterial effect of the coating. The addition of cyclohexanone can promote the light-induced cross-linking reaction, accelerate the curing speed of the coating, improve the density of the coating, prevent the invasion of microorganisms, and help the antibacterial ingredients to better disperse and diffuse in the coating, and better inhibit the attachment and reproduction of bacteria. Through the synergistic effect of the four ingredients of nano zinc oxide, eugenol, pinene alcohol and cyclohexanone, the coating not only has excellent antibacterial properties, but also can effectively inhibit the attachment, reproduction and invasion of bacteria, thereby achieving the purpose of maintaining surface hygiene for a long time.
[0008] Preferably, the mass ratio of tripropylene glycol diacrylate to neopentyl glycol diacrylate is 10:3.
[0009] In the above technical scheme, the present application further optimizes the comprehensive performance of the coating by optimizing the usage ratio of tripropylene glycol diacrylate and neopentyl glycol diacrylate, and further improves the glossiness of the coating on the basis of further enhancing the hydrophobicity and adhesion of the coating.
[0010] Preferably, the mass ratio of the nano zinc oxide, eugenol, pinene alcohol and cyclohexanone is 1.5:1.5:2:2.
[0011] In the above technical solution, the present application further enhances the antibacterial properties of the coating by optimizing the dosage ratio of nano zinc oxide, eugenol, pinene alcohol, and cyclohexanone. At this dosage ratio, nano zinc oxide, eugenol, and pinene alcohol can effectively improve the antibacterial efficiency and more effectively inhibit the growth of various bacteria and fungi. Cyclohexanone can interact with pinene alcohol at this dosage ratio, further promoting the uniform dispersion of antibacterial components in the coating, thereby further enhancing the overall antibacterial effect of the coating.
[0012] Preferably, the dispersant is a mixture of polyethylene glycol diacrylate and hexafluoroisopropanol in a mass ratio of 1:(0.2-0.5).
[0013] In the above technical solution, the present application can effectively improve the dispersibility and stability of the coating by selecting polyethylene glycol diacrylate and hexafluoroisopropanol as dispersants for antifouling and antibacterial ceramic-like coatings, thereby ensuring the uniformity of the coating during preparation and use and avoiding possible agglomeration. At the same time, the present application optimizes the dosage ratio of polyethylene glycol diacrylate and hexafluoroisopropanol, making the role of the dispersant in the coating more efficient, which is conducive to the long-term stable storage of the coating and the improvement of the construction performance.
[0014] Preferably, the photoinitiator is a mixture of 2959 photoinitiator and TPO photoinitiator in a mass ratio of (2-4): (1-2).
[0015] In the above technical scheme, the present application not only improves the curing efficiency of the coating by mixing 2959 photoinitiator and TPO photoinitiator, but also reduces the curing temperature of the coating to a certain extent, so that the coating can maintain good curing performance in a wider temperature range, and cooperates with cyclohexanone to further accelerate the curing speed of the coating, shorten the production cycle, ensure that the coating forms a denser network structure during the curing process, ensure the high density of the coating, further improve the wear resistance of the coating, isolate the invasion of bacteria to the coating, and further extend the service life of the product.
[0016] Preferably, the organic solvent is any one of acetone, ethyl acetate, isopropanol or a mixture of several of them.
[0017] In the above technical solution, the present application can effectively improve the solubility and construction performance of the coating by selecting acetone, ethyl acetate and isopropanol as organic solvents.
[0018] Preferably, the particle size of the nano-silicon carbide is 10-50 nm, and the particle size of the nano-zinc oxide is 10-30 nm.
[0019] In the above technical solution, the present application can ensure the uniform distribution and good adhesion of the filler in the coating by selecting nano silicon carbide with a particle size of 10-50nm and nano zinc oxide with a particle size of 10-30nm. The addition of nano silicon carbide not only gives the coating a texture of simulated ceramics, but also improves the hardness and wear resistance of the coating. Nano zinc oxide plays a key role in antibacterial properties, and its tiny particle size makes it more active, thereby exerting a stronger antibacterial effect.
[0020] In the second aspect, the present application provides a method for preparing an antifouling and antibacterial imitation ceramic coating using the following technical solution: A method for preparing an antifouling and antibacterial imitation ceramic coating comprises the following steps: Step 1: Mix and stir the UV-curable fingerprint easy-to-clean fluorine-containing resin and 25%-30% UV-curable hybrid silicone-fluorine polyurethane acrylic until they are evenly dispersed to obtain material 1; mix cyclohexanone, nano zinc oxide, eugenol, and pinene alcohol until they are evenly dispersed to obtain material 2; Step 2: Add tripropylene glycol diacrylate, neopentyl glycol diacrylate, photoinitiator, dispersant, nano silicon carbide and material 2 to the organic solvent in sequence, stir until mixed evenly, then add material 1 and fully disperse to obtain an antifouling and antibacterial imitation ceramic coating.
[0021] In the above technical solution, the present application ensures that various ingredients can be fully mixed and evenly formed to form a uniform imitation ceramic coating by selecting specific raw materials and preparation processes, thereby ensuring the excellent performance of the imitation ceramic coating.
[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. This application selects UV-curable fingerprint easy-to-clean fluorine-containing resin and UV-curable hybrid silicone-fluorine polyurethane acrylic as the main ingredients of anti-fouling and antibacterial ceramic-like coatings, which can effectively improve the anti-fouling performance, wear resistance, weather resistance and chemical resistance of the coating, and ensure the long-term stability and aesthetics of the coating.
[0023] 2. The present application enhances the hydrophobicity, adhesion and wear resistance of the antifouling and antibacterial ceramic-like coating by adding tripropylene glycol diacrylate and neopentyl glycol diacrylate, so that the coating has a self-cleaning effect and is not easy to be stained, scratched or leave fingerprints.
[0024] 3. This application ensures the simulated ceramic texture of the coating and improves the aesthetics of the coating by introducing nano-silicon carbide.
[0025] 4. The present application imparts broad-spectrum antibacterial properties to the coating by adding nano zinc oxide, eugenol and pinene alcohol. The addition of cyclohexanone improves the density of the coating, prevents the invasion of microorganisms, and helps the antibacterial components to be better dispersed and diffused in the coating. The synergistic effect of the four components of nano zinc oxide, eugenol, pinene alcohol and cyclohexanone makes the coating not only have excellent antibacterial properties, but also can effectively inhibit the attachment, reproduction and invasion of bacteria, thereby achieving the purpose of maintaining surface hygiene for a long time.
[0026] 5. The antifouling and antibacterial ceramic-like coating provided by the present application has good antifouling performance, antibacterial performance and wear resistance, and can meet the high standards of modern consumers for health and safety. At the same time, the antifouling and antibacterial ceramic-like coating of the present application has the advantages of fast curing speed, environmental protection and energy saving, and is suitable for promotion and application in high-end markets such as automotive interiors and home appliance shells. DETAILED DESCRIPTION
[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0028] Example 1 An antifouling and antibacterial imitation ceramic coating comprises 30kg of UV-curable fluorine-containing easy-to-clean resin, 30kg of UV-curable inorganic hybrid silicone resin, 9kg of tripropylene glycol diacrylate, 2kg of neopentyl glycol diacrylate, 4kg of photoinitiator, 3kg of dispersant, 4kg of nano silicon carbide, 2kg of nano zinc oxide, 1kg of eugenol, 1.5kg of pine alcohol, 2kg of cyclohexanone and 11.5kg of organic solvent.
[0029] Among them, the UV-curable fluorine-containing easy-to-clean resin is DSP-552F from Xiamen Aikema Chemical Co., Ltd.
[0030] Among them, the UV-curable inorganic hybrid silicone resin is UV-9828 hybrid silicone-fluorine polyurethane acrylic produced by Dongguan Inoue New Materials Development Co., Ltd.
[0031] Among them, tripropylene glycol diacrylate is TPGDA produced by Guangzhou Yuanchuang Chemical Co., Ltd.
[0032] Among them, neopentyl glycol diacrylate is NPGDA of Jiangsu Minglin Chemical Technology Co., Ltd.
[0033] The photoinitiator is a mixture of 2959 photoinitiator and TPO photoinitiator in a mass ratio of 2:1.
[0034] Among them, 2959 photoinitiator is IGM 2959 photoinitiator.
[0035] Wherein, the TPO photoinitiator is IGM TPO photoinitiator.
[0036] The dispersant is a mixture of polyethylene glycol diacrylate and hexafluoroisopropanol in a mass ratio of 1:0.2.
[0037] Among them, polyethylene glycol diacrylate is PEG(200)DA from Guangdong Yingtai New Materials Co., Ltd.
[0038] Among them, hexafluoroisopropanol comes from Maoming Xiongda Chemical Co., Ltd.
[0039] Among them, nano silicon carbide is from Shandong Jinmeng New Materials Co., Ltd., and its particle size is between 10-50nm.
[0040] Among them, nano zinc oxide is from Dongguan Tongyuan Chemical Co., Ltd., and its particle size is between 10-30nm.
[0041] Among them, eugenol comes from Xiamen Zhongnong Science and Technology New Materials Co., Ltd.
[0042] Among them, pineneol comes from Shandong Guohua Chemical Co., Ltd.
[0043] Among them, cyclohexanone is from Guangzhou Xinyang Chemical Co., Ltd.
[0044] Among them, the organic solvent is ethyl acetate, which is from Foshan Changxing New Materials Co., Ltd.
[0045] In this embodiment, a method for preparing an antifouling and antibacterial imitation ceramic coating is also provided, which specifically adopts the following steps: Step 1: Mix the UV-curable fingerprint easy-to-clean fluorine-containing resin and the UV-curable hybrid silicone-fluorine polyurethane acrylic, and stir until they are evenly dispersed to obtain material 1; mix cyclohexanone, nano zinc oxide, eugenol, and pinene alcohol until they are evenly dispersed to obtain material 2.
[0046] Step 2: Add tripropylene glycol diacrylate, neopentyl glycol diacrylate, photoinitiator, dispersant, and nano-silicon carbide to ethyl acetate in sequence, stir until mixed evenly, then add material 2, and after fully dispersed, add material 1, stir until completely mixed evenly, to obtain an antifouling and antibacterial imitation ceramic coating.
[0047] Example 2 An antifouling and antibacterial imitation ceramic coating, which is different from Example 1 in that it includes 35kg UV-curable fluorine-containing easy-to-clean resin, 25kg UV-curable inorganic hybrid silicone resin, 8kg tripropylene glycol diacrylate, 4kg neopentyl glycol diacrylate, 4.5kg photoinitiator, 3kg dispersant, 3kg nano-silicon carbide, 1kg nano-zinc oxide, 1.5kg eugenol, 1kg pine alcohol, 3kg cyclohexanone, and 11kg organic solvent.
[0048] The photoinitiator is a mixture of 2959 photoinitiator and TPO photoinitiator in a mass ratio of 3:1.5.
[0049] The dispersant is a mixture of polyethylene glycol diacrylate and hexafluoroisopropanol in a mass ratio of 1:0.5.
[0050] Example 3 An antifouling and antibacterial imitation ceramic coating, which is different from Example 1 in that it includes 30kg UV-curable fluorine-containing easy-to-clean resin, 25kg UV-curable inorganic hybrid silicone resin, 10kg tripropylene glycol diacrylate, 3kg neopentyl glycol diacrylate, 5kg photoinitiator, 4kg dispersant, 5kg nano-silicon carbide, 1.5kg nano-zinc oxide, 1.5kg eugenol, 2kg pine alcohol, 2kg cyclohexanone, and 11kg organic solvent.
[0051] The photoinitiator is a mixture of 2959 photoinitiator and TPO photoinitiator in a mass ratio of 4:1.
[0052] The dispersant is a mixture of polyethylene glycol diacrylate and hexafluoroisopropanol in a mass ratio of 1:0.4.
[0053] Example 4 An antifouling and antibacterial imitation ceramic coating, which is different from Example 1 in that the dispersant is Lubrizol SOLSPERSE 24000 dispersant.
[0054] Comparative Example 1 An antifouling and antibacterial imitation ceramic coating, which is different from Example 1 in that tripropylene glycol diacrylate is replaced by trimethylolpropane triacrylate in an equal amount.
[0055] Comparative Example 2 An antifouling and antibacterial imitation ceramic coating, which is different from Example 1 in that neopentyl glycol diacrylate is replaced by hexanediol diacrylate in an equal amount.
[0056] Comparative Example 3 An antifouling and antibacterial imitation ceramic coating, which is different from Example 1 in that an equal amount of nano zinc oxide is replaced by nano silver oxide, and the particle size is between 10-30 nm.
[0057] Comparative Example 4 An antifouling and antibacterial imitation ceramic coating, which is different from Example 1 in that eugenol and pineol are replaced by nano silver oxide in equal amounts.
[0058] Comparative Example 5 An antifouling and antibacterial imitation ceramic coating, which is different from Example 1 in that cyclohexanone is replaced by acetone in equal amounts.
[0059] Performance testing: In order to verify the performance of the antifouling and antibacterial imitation ceramic coating of the present application, the coating samples of Examples 1 to 4 and Comparative Examples 1 to 5 were subjected to the following performance tests: The pencil hardness of the imitation ceramic coating was tested with reference to GB / T 6739-2022; the adhesion of the imitation ceramic coating was tested with reference to GB / T9286-1998 (PP substrate); the wear resistance of the imitation ceramic coating was tested with reference to GB / T1768-1979 (250g weight, rubber grinding wheel, 100r cycle test); the antibacterial rate of the imitation ceramic coating against Staphylococcus aureus and Escherichia coli was tested with reference to GB / T 21866-2008; three kinds of pollutants, soy sauce, coffee and oily handwriting, were added to the surface of the imitation ceramic coating respectively, and after 24 hours, the coating was wiped with a dust-free cloth, the removal of the pollutants was observed, and the anti-fouling ability was evaluated.
[0060] The above test results are shown in Tables 1 and 2.
[0061] Table 1: Table 2: The experimental results of the coating samples of Examples 1 to 4 and Comparative Examples 1 to 5 were analyzed. The coating samples of Examples 1 to 4 performed well in pencil hardness, adhesion, wear resistance, antibacterial rate and decontamination. It can be seen that the imitation ceramic coatings of the embodiments of the present application have good anti-fouling, antibacterial and wear resistance.
[0062] Specifically analyzing in combination with Example 1 and Comparative Examples 1 to 2, the difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not use tripropylene glycol diacrylate, and the difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not use neopentyl glycol diacrylate. Example 1 performs well in adhesion, wear resistance and decontamination performance. It can be seen that further introducing tripropylene glycol diacrylate and neopentyl glycol diacrylate into the imitation ceramic coating of the present application can further enhance the adhesion, wear resistance and decontamination ability of the coating.
[0063] Specifically combined with Example 1 and Comparative Examples 3 to 5, Comparative Examples 3 and 4 respectively replaced nano zinc oxide and eugenol and pinene alcohol with nano silver oxide compared to Example 1, and Comparative Example 5 replaced cyclohexanone with acetone. Example 1 performed well in terms of antibacterial and wear resistance. This shows that nano zinc oxide, eugenol, and pinene alcohol play a key role in the ceramic-like coating of the present application, and their presence is crucial to improving the antibacterial properties of the coating, while the addition of cyclohexanone can promote the uniform dispersion of antibacterial components and improve the density of the coating, improve the wear resistance of the coating, and prevent the invasion of microorganisms.
[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An antifouling and antibacterial imitation ceramic coating, characterized in that: The invention comprises the following components in percentage by mass: 30%-40% UV-curable fingerprint easy-to-clean fluorine-containing resin, 25%-30% UV-curable hybrid silicon-fluorine polyurethane acrylate, 8%-12% tripropylene glycol diacrylate, 2%-4% neopentyl glycol diacrylate, 3%-6% photoinitiator, 3%-5% dispersant, 3%-5% nano silicon carbide, 1%-2% nano zinc oxide, 1%-2% eugenol, 1%-2% pine oil, 2%-3% cyclohexanone and 10%-20% organic solvent.
2. The antifouling and antibacterial imitation ceramic coating according to claim 1, characterized in that: The mass ratio of the tripropylene glycol diacrylate to the neopentyl glycol diacrylate is 10:
3.
3. The antifouling and antibacterial imitation ceramic coating according to claim 1, characterized in that: The mass ratio of the nano zinc oxide, eugenol, pinene alcohol and cyclohexanone is 1.5:1.5:2:
2.
4. The antifouling and antibacterial imitation ceramic coating according to claim 1, characterized in that: The dispersant is prepared by mixing polyethylene glycol diacrylate and hexafluoroisopropanol in a mass ratio of 1:(0.2-0.5).
5. The antifouling and antibacterial imitation ceramic coating according to claim 1, characterized in that: The photoinitiator is prepared by mixing 2959 photoinitiator and TPO photoinitiator in a mass ratio of (2-4): (1-2).
6. The antifouling and antibacterial imitation ceramic coating according to claim 1, characterized in that: The organic solvent is any one of acetone, ethyl acetate and isopropanol or a mixture of several of them.
7. The antifouling and antibacterial imitation ceramic coating according to claim 1, characterized in that: The particle size of the nano silicon carbide is 10-50nm, and the particle size of the nano zinc oxide is 10-30nm.
8. A method for preparing the antifouling and antibacterial ceramic-like coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Mix UV-curable fingerprint easy-to-clean fluorine-containing resin and 25%-30% UV-curable hybrid silicone-fluorine polyurethane acrylic and stir until they are evenly dispersed to obtain material 1; mix cyclohexanone, nano zinc oxide, eugenol, and pinene alcohol until they are evenly dispersed to obtain material 2; Step 2: Add tripropylene glycol diacrylate, neopentyl glycol diacrylate, photoinitiator, dispersant, nano silicon carbide and material 2 to the organic solvent in sequence, stir until mixed evenly, then add material 1 and fully disperse to obtain an antifouling and antibacterial imitation ceramic coating.
Citation Information
Patent Citations
Water-based ultraviolet-curing anti-fingerprint coating and preparation method thereof
CN108300274A
Fluorine-silicon composite photocatalytic antibacterial antifouling coating material and preparation method thereof
CN111187548A
Anti-fingerprint high-solid low-viscosity wear-resistant ceramic-like photocureable coating and preparation method thereof
CN114437616A
Odor and colorant stabilized compositions
WO2024027931A1
Compositions comprising an antimicrobial boosting agent
WO2024028512A1